Elmer's special day [anglicky] - McKee, David (Andersen, 2011)
Elmer, the patchwork elephant, looked at the other elephants, and smiled. It was almost Elmer´s Day - the day when once a year all elephants decorate themselves and parade. The elephants had only just begun to prepare for it, but they were already excited and noisy.